2016
DOI: 10.1177/1757975916639870
|View full text |Cite
|
Sign up to set email alerts
|

Individual, social-environmental, and physical-environmental factors that underlie sense of coherence in Dutch adults

Abstract: Antonovsky's salutogenesis is a theoretical perspective on health development that explores physical, mental, and social factors that contribute to a 'healthy life orientation' and also a theoretical approach to behavior change. Previous studies applying salutogenesis show that a high sense of coherence (SOC), a composite measure from salutogenesis indicating one's capacity to cope with stress, is associated with a healthy life orientation and lifestyle behaviors, including healthy eating patterns. However, li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
2
6
0
1
Order By: Relevance
“…SOC scores appear to be in line with data collected with this scale in a study of 781 Dutch persons of 18 years and older, which showed high SOC for 386 persons and low SOC for 395 persons (Swan et al 2016). No significant change of SOC scores occurred.…”
Section: Discussion Of Main Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…SOC scores appear to be in line with data collected with this scale in a study of 781 Dutch persons of 18 years and older, which showed high SOC for 386 persons and low SOC for 395 persons (Swan et al 2016). No significant change of SOC scores occurred.…”
Section: Discussion Of Main Resultssupporting
confidence: 69%
“…Scores on SOC were calculated by adding up the points (1-7) marked for each item. Similar to previous research with this scale in the Netherlands, we rated SOC ≤ 67 as "low" and SOC ≥ 68 as "high" (Swan et al 2016).…”
Section: Analysis Of Data About Citizen Scientistsmentioning
confidence: 79%
“…Innovations in behaviour change theory and what health means for individuals can be helpful in this. An example of this is the application of the Salutogenic Framework to Nutrition Research and Practice (147)(148)(149)(150)(151)(152). The definition of health is in discussion in science, and changing (153,154).…”
Section: Importance Of Both Qualitative Research and Quantitative Resmentioning
confidence: 99%
“…Life experiences that mattered to the women who participated in our study were maintaining control of their daily lives and making their own decisions. Similarly, Swan et al (39) found a correlation between a high SOC and empowerment. The authors concluded that empowerment supported the individuals who relied on their skills, resources, opportunities and authority to manage their everyday lives.…”
Section: Relying On Inner Logics and Maintaining Controlmentioning
confidence: 86%
“…The women found meaningfulness in relying on their own interpretation of their health status. Several studies indicate that managing a potential stressor through self-interpretation seems to be meaningful when facing a screening invitation and deciding not to attend the screening (20,38,39). According to the review of Stol et al (38), people who feel healthy and t have no concerns about their health status and consider their cardiovascular risk to be low.…”
Section: Relying On Inner Logics and Maintaining Controlmentioning
confidence: 99%